Syndecan-4 is a key determinant of collagen cross-linking and passive myocardial stiffness in the pressure-overloaded heart. (13th January 2015) - Herum, Kate M.; Lunde, Ida G.; Skrbic, Biljana; Louch, William E.; Hasic, Almira; Boye, Sigurd; Unger, Andreas; Brorson, Sverre-Henning; Sjaastad, Ivar; Tønnessen, Theis; Linke, Wolfgang A.; Gomez, Maria F.; et al.
Abstract: Aims: Diastolic dysfunction is central to the development of heart failure. To date, there is no effective treatment and only limited understanding of its molecular basis. Recently, we showed that the transmembrane proteoglycan syndecan-4 increases in the left ventricle after pressure overload in mice and man, and that syndecan-4 via calcineurin/nuclear factor of activated T-cells (NFAT) promotes myofibroblast differentiation and collagen production upon mechanical stress. The aim of this study was to investigate whether syndecan-4 affects collagen cross-linking and myocardial stiffening in the pressure-overloaded heart. Methods and results: Aortic banding (AB) caused concentric hypertrophy and increased passive tension of left ventricular muscle strips, responses that were blunted in syndecan-4 −/− mice. Disruption of titin anchoring by salt extraction of actin and myosin filaments revealed that the effect of syndecan-4 on passive tension was due to extracellular matrix remodelling. Expression and activity of the cross-linking enzyme lysyl oxidase (LOX) increased with mechanical stress and was lower in left ventricles and cardiac fibroblasts from syndecan-4 −/− mice, which exhibited less collagen cross-linking after AB. Expression of osteopontin (OPN), a matricellular protein able to induce LOX in cardiac fibroblasts, was up-regulated in hearts after AB, in mechanically stressed fibroblasts and in fibroblasts overexpressing syndecan-4, calcineurin, or NFAT, but down-regulated in fibroblasts lacking syndecan-4 or after NFAT inhibition. Interestingly, the extracellular domain of syndecan-4 facilitated LOX-mediated collagen cross-linking. Conclusions: Syndecan-4 exerts a dual role in collagen cross-linking, one involving its cytosolic domain and NFAT signalling leading to collagen, OPN, and LOX induction in cardiac fibroblasts; the other involving the extracellular domain promoting LOX-dependent cross-linking.